The Influence of Profitability and Liquidity on Firm Value with Firm Size as a Moderating Variable - Maharani Putri Rahmawati; Syafrizal Ikram (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the effect of profitability and liquidity on firm value, with firm size as a moderating variable, in technology sector companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach with a moderated regression analysis (MRA) model, this study employs panel data from 19 technology companies over the period 2022–2024, resulting in 57 observations. Data analysis was conducted using Eviews 13 after passing classical assumption tests. Profitability (ROA) has a positive and significant effect on firm value (? = 0.3847; p = 0.000), while liquidity (CR) does not significantly affect firm value (? = -0.0024; p = 0.2547). Firm size strengthens the positive relationship between profitability and firm value (? interaction = 0.0158; p = 0.0128), but does not moderate the relationship between liquidity and firm value (? interaction = 0.0001; p = 0.4134). The model explains 71.54% of the variation in firm value (R² = 0.7154). Profitability is a key driver of firm value in the technology sector, whereas liquidity does not play a significant role. Firm size acts as a positive moderator only for the profitability value relationship. These findings suggest that technology companies should prioritize improving profitability and leveraging scale to enhance market valuation, rather than focusing excessively on liquidity management. The study contributes to signaling theory by confirming the relevance of profitability as a value signal, particularly in large technology firms.